Revisiting Basic School Social Studies and Human Value Education Curriculum in Nepal - Shah, Rajendra Kumar (AMC Journal, 2023)
Social studies were already taught in schools in Nepal, and the contents of human values education have recently been incorporated into social studies. In the context of Nepal, this subject is completely new and it is necessary to study whether the implementation of the Basic School social studies and human value education curriculum including learning outcomes, content, teaching methods, and assessment procedures of this subject is effective. For this purpose, a mixed method has been used in this study. First of all, data and information were collected using a survey questionnaire. Thus, this study can be termed as a descriptive survey method. Secondly, an in-depth interview was also conducted to explore the perceptions of the respondents. Thus, this study may be termed a general qualitative method. Convenient sampling was used as a sampling procedure. Thirty social studies and human value education teachers from Basic Schools were selected as samples in this study. The findings of the present study reveal that there is a big gap between the philosophy of social studies and human values education curriculum and the social norms, values, and culture of Nepali society. Therefore, it is challenging to implement this curriculum effectively. Similarly, in the dissemination of the curriculum, the concept of the new curriculum has not been reached to all the teachers across the country. The findings of the present study further indicated that the learning outcomes, contents, and pedagogical practices of the curriculum should be improved. Last but not least, the role of parents, stakeholders, and students is crucial in the implementation of the Basic School social studies and human value education curriculum.